2001
DOI: 10.1111/1467-8624.00292
|View full text |Cite
|
Sign up to set email alerts
|

“I Got Some Swords and You're Dead!”: Violent Fantasy, Antisocial Behavior, Friendship, and Moral Sensibility in Young Children

Abstract: Relations between an early interest in violent fantasy and children's social understanding, antisocial and emotional behavior, and interactions with friends were investigated in 40 "hard-to-manage" preschoolers and 40 control children matched for gender, age, and school and ethnic background. Children were filmed alone in a room with a friend, and tested on a battery of cognitive tests, including false-belief, executive function, and emotion understanding tasks. Teachers reported on their friendship quality. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 44 publications
(49 reference statements)
5
74
1
2
Order By: Relevance
“…In a study with elementary-and middle-school-age children living in urban neighborhoods, Guerra et al [2003] found positive links between violence exposure, violent fantasy, and aggressive behavior. Dunn and Hughes [2001] found that, compared to a control group, a group of preschool-age children who scored high on a conduct disorder scale exhibited higher rates of violent fantasy as assessed through pretend play episodes. In a related study on engagement in toy-weapon play, Watson and Peng [1992] found that pretend aggression was associated with increased real aggression rather than having a cathartic effect of reducing it.…”
Section: The Fantasy-aggression Linkmentioning
confidence: 87%
“…In a study with elementary-and middle-school-age children living in urban neighborhoods, Guerra et al [2003] found positive links between violence exposure, violent fantasy, and aggressive behavior. Dunn and Hughes [2001] found that, compared to a control group, a group of preschool-age children who scored high on a conduct disorder scale exhibited higher rates of violent fantasy as assessed through pretend play episodes. In a related study on engagement in toy-weapon play, Watson and Peng [1992] found that pretend aggression was associated with increased real aggression rather than having a cathartic effect of reducing it.…”
Section: The Fantasy-aggression Linkmentioning
confidence: 87%
“…As noted by Davey (2011) disruptive behavior result to impaired academic achievement, which usually leads to conflict with classmates. In line with this Coplan Gauinski-Molins, Lagace-Seguin and Wichman (2001), and Dunn and Hughes (2001) noted that children who persist in immature forms of solitary play such as wandering around aimlessly are at risk of manifesting disruptive behaviors.…”
Section: An Overview Of the Studymentioning
confidence: 79%
“…The increased academic and social demands of formal schooling, as well as standards for behaviors are required from children are not usually met (Dunn & Hughes, 2001). Teachers report that these types of children have difficulty in working independently and also lack organization.…”
Section: An Overview Of the Studymentioning
confidence: 99%
“…Children's gender-typed preferences for toys grow larger with development (Golombok & Hines, 2002); studies conducted in the US (Goldberg, Kashy & Smith, 2012), Sweden (Nelson, 2005) or the UK (Dunn & Hughes, 2001) have reported consistent patterns, indicating that girls prefer dolls, stuffed animals and educational toys, whereas boys prefer vehicles, action figures, tool sets or construction toys. In addition to differences in preferences, boys and girls show a stronger bias for toys stereotyped as own-gender than for cross-gender-typed or gender-neutral toys (Cherney, KellyVance, Gill, Ruane & Ryalls, 2003).…”
Section: Research On Gender-typed Objects Preferencesmentioning
confidence: 99%